2011
DOI: 10.1007/s00432-011-0997-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal disease detection in peripheral blood and bone marrow from patients with non-metastatic neuroblastoma

Abstract: Minimal disease detection in PB seems to be useful for predicting relapse probabilities in patients with non-metastatic NB. The stages 1 and 2 patients with neuroblastoma showed high survival rates, and MD was detected in a small number of patients probably being non-contributory for predicting patient outcome. For stage 3 patients with NB, MD detection by QRT-PCR in PB at diagnosis could be useful for predicting outcome and for early and sensitive detection of relapsing disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…As suggested for anti-GD2 antibody and metaiodobenzylguanidine (MIBG) therapies (11), the various treatment protocols might affect these inconsistencies. Although the quantity of MRD in PB and/or BM samples predicts tumor relapse and patient outcome, conflicting results have been reported with regard to the prognostic value of MRD monitoring using various MRD markers (14)(15)(16). Given that CTCs in the PB and DTCs in the BM define the main faces of MRD in the clinics, these inconsistencies may imply genetic and phenotypic heterogeneity of CTCs and DTCs (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested for anti-GD2 antibody and metaiodobenzylguanidine (MIBG) therapies (11), the various treatment protocols might affect these inconsistencies. Although the quantity of MRD in PB and/or BM samples predicts tumor relapse and patient outcome, conflicting results have been reported with regard to the prognostic value of MRD monitoring using various MRD markers (14)(15)(16). Given that CTCs in the PB and DTCs in the BM define the main faces of MRD in the clinics, these inconsistencies may imply genetic and phenotypic heterogeneity of CTCs and DTCs (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rationale for introducing the current protocols into the clinics remains unclear (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…These protocols used various sets and quantities of MRD markers, including 3 markers (DCX, PHOX2B and TH) (4), 5 markers (CHGA, DCX, DDC, PHOX2B and TH) (5), 6 markers (CHRNA3, DBH, DDC, GAP43, PHOX2B and TH) (6), 7 markers (B4GALNT1, DCX, DDC, ELAV4, PHOX2B, STX and TH) (7), 8 markers (CCND1, CRMP1, DDC, GABRB3, ISL1, KIF1A, PHOX2B and TACC2) (8), and 11 markers (CHRNA3, CRMP1, DBH, DCX, DDC, GABRB3, GAP43, ISL1, KIF1A, PHOX2B and TH) (9). The clinical significance of MRD monitoring in neuroblastoma patients remains to be established (5,7,10,11). The present study reports two high-risk neuroblastoma patients whose MRD was consecutively monitored using 11 markers (CHRNA3, CRMP1, DBH, DCX, DDC, GABRB3, GAP43, ISL1, KIF1A, PHOX2B and TH) during their course of treatment (9).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that TH expression at diagnosis might be a significant factor in future methods of risk stratification for NB. Some studies examined the clinical implication of positive TH expression in non-metastatic NB [19,23]. Yanez et al [23] reported an association of positive TH expression in PB at diagnosis with a higher probability of relapse in patients with non-metastatic NB.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies examined the clinical implication of positive TH expression in non-metastatic NB [19,23]. Yanez et al [23] reported an association of positive TH expression in PB at diagnosis with a higher probability of relapse in patients with non-metastatic NB. These findings suggest that some patients with localized tumors (by conventional diagnostic modalities) might have disseminated micrometastatic disease and therefore might benefit from upstaging and more aggressive treatment [24].…”
Section: Discussionmentioning
confidence: 99%